MENGHADAPI PANDEMI COVID-19: BELAJAR DARI PERISTIWA PEMBUANGAN BABEL - Silvester Manca (STIPAS St. Sirilus Ruteng, 2022)
The aims of this studi to describe the meaning of the Babylon displays in the Christian Biblical in the face of the pandemic covid-19. By using the library study, the researcher to explain the bindel disposal as a major crisis in the history of the Israelities and to discribe the actual meaning of the event in the context powermination of pandemic covid-19who still threaten in the world. It was found that at least there are twi important learning of the Babylon disposal even of the pandemic covid-19, namely creativity, inovation, and the hope. The Babylon disposal teach about a creativty and inovative and optimistic attitudes in the pandemic covid-19.